Storytelling in the Digital Age: Examining the Role and Effectiveness in Communication Strategies of Social Media Content Creators - Ermy Pertiwi; Ary Putra Sanusi (Palakka : Media and Islamic Communication, 2023)
This research examines the factors influencing storytelling effectiveness in social media content creation. The research objectives are to explore the role of storytelling and understand its impact on content creation strategies. A case study approach is employed, with a purposively selected content creator as the primary participant. In-depth interviews are conducted, and thematic analysis is used to analyze the data. Findings highlight the importance of authenticity, relatability, and visual appeal in engaging the audience. Real experiences and values establish trust and connections with the audience, while high-quality visuals enhance the storytelling experience. Emotional engagement, concise storytelling, and active audience engagement also emerge as key factors. The research contributes to understanding effective communication strategies for content creators on social media platforms. By leveraging authenticity, relatability, visual appeal, emotional engagement, concise storytelling, and active audience engagement, content creators can enhance their storytelling strategies. The study acknowledges the limitations of a single case study and subjective interpretations.